H-infinity approach to design optimal output control for the aggregated interpolation model of helicopter motion. Issue 1 (September 2020) - Kudryavtseva, I; Efremov, A; Panteleev, A
Abstract: This paper presents the problem of designing a feedback control of the aggregated model describing helicopter flight dynamics under the influence of exogenous factors based on the H-infinity approach. The original nonlinear equations of dynamics are assumed to be linearized regarding to several flight modes that characterize with a set of precisely specified flight conditions such as an attitude of an aircraft, its forward speed and turn rate. Matrices of the linearized systems are dependent on the speed of the aircraft. Due to that the aggregated model comprises eight submodels corresponding to flight modes when the speed varies from hover to 140 kts in a certain regular interval. The proposed principle of designing includes two stages: on the first stage the feedback control input is selected for each submodel separately so that the H-infinity norm of the value functional with respect to the H-infinity norm of disturbances is minimum; on the second one the interpolation technique lying in the expansion of matrices in the basis of finite functions is applied. The solution method is experienced on three helicopter models: ZD559-Lynx, the twin engine, utility helicopter in the 4.5 -ton category; S123-Bo105, the twin engine helicopter in the 2.5 ton class; SA330-Puma, the twin engine, medium-support helicopter in the 6-ton category.